Proton Therapy in Supradiaphragmatic Lymphoma: Predicting Treatment-Related Mortality to Help Optimize Patient Selection - Ntentas, Georgios; Dedeckova, Katerina; Andrlik, Michal; Aznar, Marianne C; Shakir, Rebecca; Ramroth, Johanna; Begum, Rubina; Kubeš, Jiří; Darby, Sarah C; Mikhaeel, N George; Cutter, David J (International journal of radiation oncology, biology, physics, 2022)
PURPOSE: In some patients with Hodgkin lymphoma (HL), proton beam therapy (PBT) may reduce the risk of radiation-related cardiovascular disease (CVD) and second cancers (SC) compared with photon radiation therapy (RT). Our aim was to identify patients who benefit the most from PBT in terms of predicted 30-year absolute mortality risks (AMR30) from CVD and SC, taking into account individual background, chemotherapy, radiation, and smoking-related risks. METHODS AND MATERIALS: Eighty patients with supradiaphragmatic HL treated with PBT between 2015 and 2019 were replanned using optimal photon RT. To identify patients predicted to derive the greatest benefit from PBT compared with photon RT, doses and AMR30 from CVD and SC of the lung, breast, and esophagus were compared for all patients and across patient subgroups. RESULTS: For patients with mediastinal disease below the origin of the left main coronary artery (n = 66; 82%), PBT reduced the mean dose to the heart, left ventricle, and heart valves by 1.0, 2.7, and 3.6 Gy, respectively. Based on U.S. mortality rates, PBT reduced CVD AMR30 by 0.2%, from 5.9% to 5.7%. The benefit was larger if the mediastinal disease overlapped longitudinally with the heart by ≥40% (n = 23; 29%). PBT reduced the mean dose to the heart, left ventricle, and heart valves by 3.2, 5.6, and 5.1 Gy, respectively, and reduced CVD AMR30 by 0.8%, from 7.0% to 6.2%. For patients with axillary disease (n = 25; 31%), PBT reduced the mean lung dose by 2.8 Gy and lung cancer AMR30 by 0.6%, from 2.7% to 2.1%. Breast and esophageal doses were also lower with PBT, but the effects on AMR30 were negligible. The effect of smoking on CVD and lung cancer AMR30 was much larger than radiation and chemotherapy and the differences between radiation modalities. CONCLUSIONS: The predicted benefit of PBT is not universal and limited to certain categories of patients with lymphoma and lower mediastinal or axillary disease. Smoking cessation should be strongly encouraged in smokers who require thoracic RT.
Keywords: Radiotherapy Dosage; celková dávka radioterapie; Proton Therapy; Smoking; Hodgkinova nemoc; kouření; Humans; Patient Selection; protonová terapie; Hodgkin Disease; lidé; výběr pacientů